MODEL PEMBINAAN TENAGA KERJA WANITA PRODUKTIF PADA RUMAHTANGGA NELAYAN SEBAGAI UPAYA PENINGKATAN KETAHANAN EKONOMI MASYARAKAT PESISIR DAN PULAU-PULAU KECIL - Sugiarti, Asti (Journal Galung Tropika, 2014)
This research  was  aimed  to obtain the  empowering  model of productive womenlabour as  an  effort  to  improve coastal society economics  sustainability. Research was carried out for six-month from June to November 2012 in coastal and small islands of Pangkep Regency, South Sulawesi, using elaboration of data and information of field (explored field research). Each district residing in the small island and seaboard taken as a  sample of household fisherman.There were50  household in total  as responders.  The purpose  of this research is to  create  a model  programmeof  economical developmentfor society in the small islands and coastal region in term of  improving their economical sustainability that are vulnerable in today’s world.Other than that, its also meant to create a development pattern of society’s alternative living source, especially for the future women’s generation in the coastal household that are still productive and has the sparetime that could be used to do much needed economical activities. The early data shown that the education level of the responders are averagely low, with majority of zero educational background or have not completed the elementary school level. And so does the variety of job that are limited to become a labour fastener of sea grassor managing the household activities only. Even on some of the other, 14% of them are still unemployed and did not have sufficient source to support their lives.  Byapplicating the development programme to achieve economical sustainability, there are promising chances to explore other alternative living source in non fishery sector, with the final result of empowered women and coastal society.